2004
DOI: 10.1242/jeb.01306
|View full text |Cite
|
Sign up to set email alerts
|

Floral scents induce recall of navigational and visual memories in honeybees

Abstract: During foraging flights, honeybees learn visual and chemical cues associated with a food source. We investigated whether learned olfactory cues can trigger visual and navigational memories in honeybees that assist them in navigating back to a known food source. In a series of experiments, marked bees were trained to forage at one or more sugar water feeders, placed at different outdoor locations and carrying different scents or colours. We then tested the ability of these bees to recall the locations (or colou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 43 publications
1
55
1
1
Order By: Relevance
“…Although cross-modal effects of experience on the behavioral level have been shown in honeybees and crickets by using associative learning paradigms (37)(38)(39), our study shows, in addition, a cross-modal effect of experience on the central nervous level in an insect. The observed behavioral increase in sensitivity across modalities seems to originate at least partially from the interaction in a primary sensory integration center, and similar phenomena have so far only been described in higher-order brain centers in vertebrates (17,18).…”
Section: Discussioncontrasting
confidence: 70%
“…Although cross-modal effects of experience on the behavioral level have been shown in honeybees and crickets by using associative learning paradigms (37)(38)(39), our study shows, in addition, a cross-modal effect of experience on the central nervous level in an insect. The observed behavioral increase in sensitivity across modalities seems to originate at least partially from the interaction in a primary sensory integration center, and similar phenomena have so far only been described in higher-order brain centers in vertebrates (17,18).…”
Section: Discussioncontrasting
confidence: 70%
“…The injection of a compound containing three odorant scents, tricosane, pentacosane and Z-(9)-tricosene, into the hive increased the number of worker bees exiting the hive, presumably foraging. Reinhard et al (Reinhard et al, 2004a;Reinhard et al, 2004b) showed that odors can be a trigger leading honeybees to recall the feeders they have visited. Therefore, dance scent might influence mass change as a result of forages of bees that were activated by dance scent.…”
Section: Effects Of Dance On Food Collectionmentioning
confidence: 99%
“…Flying insects are capable of agile flight at low speeds, complex obstacle avoidance, vertical take-off and landing, and hovering for long periods at a time. Recent studies with bees show they can estimate flight duration, regulate flight speed, and land using visual processing [1][2][3]. Beyond having the same impressive flying skills as other flying insects, honeybees achieve cognitively sophisticated behaviors despite the very limited size of their brain (approximately 10 6 neurons) [4].…”
Section: Introductionmentioning
confidence: 99%